2012
DOI: 10.1093/bja/aes089
|View full text |Cite
|
Sign up to set email alerts
|

Delayed subdural haematoma complicated by abducens nerve palsy and cortical vein thrombosis after obstetric epidural anaesthesia

Abstract: not consistent with C5 and 6 root damage alone. In these cases, a surgical aetiology should be sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Of the 114 reviewed cases, 19 epidural blood patches (EBPs) were used: 2 before diplopia onset, 9,24 7 during the first 24 hours after diplopia onset, 8,17,[25][26][27][28][29] and 8 EBPs 24 hours after diplopia onset. 2,27,[30][31][32][33][34][35] The other cases were not notified in time to undertake EBP. 2,36 Finally, 9.63% of the patients required an eye patch, and 5.25% needed a prism glass.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 114 reviewed cases, 19 epidural blood patches (EBPs) were used: 2 before diplopia onset, 9,24 7 during the first 24 hours after diplopia onset, 8,17,[25][26][27][28][29] and 8 EBPs 24 hours after diplopia onset. 2,27,[30][31][32][33][34][35] The other cases were not notified in time to undertake EBP. 2,36 Finally, 9.63% of the patients required an eye patch, and 5.25% needed a prism glass.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies looking at behavioral aspects of women in preparation for labor and childbirth have shown that the negative experience and pain of labor and childbirth could be reduced by encouraging women to believe they can cope with the pain [68][69][70][71][72][73], having the presence of …”
Section: Cognitive and Functional Aspects Of Labor Painmentioning
confidence: 99%
“…Clinically, opinion is divided as to whether these opioidinduced fetal heart rate changes are important. Case reports have described women requiring emergency CS for persistent fetal bradycardia following administration of intrathecal fentanyl [71], but trials and a meta-analysis have failed to show any 84 G.M. Stocks and S.K.…”
Section: Fetal Heart Rate Changesmentioning
confidence: 99%
See 2 more Smart Citations